Technical report: Inter‐ and intra‐rater reliability of regional gastrointestinal transit times measured using the 3D‐Transit electromagnet tracking system. Issue 11 (4th July 2018) - Kalsi, G. K.; Grønlund, D.; Martin, J.; Drewes, A. M.; Scott, S. M.; Birch, M. J.
Abstract: Background: The 3D‐Transit electromagnet tracking system is an emerging tool for the ambulatory assessment of gastrointestinal (GI) transit times and motility patterns, based on the anatomical localization of ingestible electromagnetic capsules. Currently, 3D‐Transit recordings are manually analyzed to extract GI transit times. As this is a subjective method, there is some inherent variability in the measurements, which may be experience‐dependent. We therefore assessed inter‐ and intra‐rater reliability of GI transit times from 3D‐Transit recordings. Methods: Thirty‐six 3D‐Transit recordings (17 female; median age: 34 years [range: 21–80]) were analyzed twice by 3 raters with varying experience. Each rater manually identified the timestamps when a capsule progressed from antrum to duodenum, and from ileum to right colon. These timestamps, along with the ingestion and expulsion times, were used to determine whole gut (WGTT), gastric emptying (GET), small intestinal (SITT) and colonic (CTT) transit times. Reliability was determined using interclass correlation coefficients (ICCs). Key Results: For capsule progression timestamps, the most and mid‐experienced raters had fair to good inter‐ and excellent intra‐rater reliability (ICCmin‐max  = 0.61‐1.00), whereas the inexperienced rater had poor to fair inter‐ and poor intra‐rater reliability (ICCmin‐max  = 0.28‐0.55). GET and SITT reliability between the most and mid‐experienced raters was fair (ICCmin‐max  = 0.61‐0.73), while reliability between these raters and the inexperienced rater was poor to fair (ICCmin‐max  = 0.28‐0.55). CTT reliability was excellent between and within all raters (ICCmin‐max  = 0.92‐0.99). Conclusions & Inferences: Inexperienced raters provide the least reliable measurements from 3D‐Transit recordings, which confirms requirement for adequate training. Automation may improve the reliability of measurements. Abstract : This study assessed the reliability of regional gastrointestinal transit times as measured by experienced and inexperienced raters using the 3D‐Transit electromagnet system. The reliability of whole gut (WGTT) and colonic transit times (CTT) was excellent across all raters. Gastric emptying (GET) and small intestinal transit time (SITT) reliability was fair between the most and mid‐experienced raters but poor for the inexperienced rater indicating a need to define minimum training standards.